1998
DOI: 10.1007/s001250051005
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of severe hypoglycaemia in diabetic children and adolescents with impaired and normal awareness of hypoglycaemia

Abstract: The goal of the treatment for Type I (insulin-dependent) diabetes mellitus is to achieve near-normal glycaemia as early as possible in as many patients as is safely possible. Hypoglycaemia is the most common and dangerous side effect of insulin treatment and the prevalence of severe episodes remains a major obstacle in attempts to prevent long-term diabetic complications with intensive insulin therapy. The Diabetes Control and Complications Trial has recently shown that intensification of insulin therapy incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 36 publications
(35 reference statements)
2
20
0
Order By: Relevance
“…Our rates of impaired awareness of hypoglycemia are consistent with those in a previous study reported by Barkai et al (13). In this prospective study of 130 children and adolescents with type 1 diabetes, impaired awareness was reported by 37% of patients.…”
Section: Discussionsupporting
confidence: 93%
“…Our rates of impaired awareness of hypoglycemia are consistent with those in a previous study reported by Barkai et al (13). In this prospective study of 130 children and adolescents with type 1 diabetes, impaired awareness was reported by 37% of patients.…”
Section: Discussionsupporting
confidence: 93%
“…Approximately two thirds of the three hypoglycemic events produce blood glucose Ͻ 35 mg/dL, and only one of 56 hypoglycemic animals died. Second, there is evidence that counter-regulatory responses to hypoglycemia may be impaired in diabetic children, especially those who experience hypoglycemia (27). Autonomic ganglion blockade simulates impairment of counter-regulatory response to hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…5,31 The presence of previous episodes may help to identify patients at greater risk for developing acute complications. 23,34 Acute complications in children with type 1 diabetes increase directly and indirectly 25,35 the costs of care. Direct medical care charges associated with DKA episodes represent 28% of the direct medical care charges for all patients, and 56% for those with recurrent DKAs.…”
Section: Complication Predictors In Pediatric Diabetesmentioning
confidence: 99%